2022
DOI: 10.5858/arpa.2021-0475-oa
|View full text |Cite
|
Sign up to set email alerts
|

Combined Infiltrative Macroscopic Growth Pattern and Infiltrative Microscopic Tumor Border Status Is a Novel Surrogate Marker of Poor Prognosis in Patients With Pancreatic Neuroendocrine Tumor

Abstract: Context.— Pancreatic neuroendocrine tumors (PanNETs) are heterogeneous tumors with a wide range of malignant potential. Therefore, identification of prognostic factors is essential. Objective.— To systematically assess the significance of tumor border, a well-known prognostic indicator in other cancers, in the PanNETs. Design.— We evaluated the macroscopic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…In the current study, tumor cells in the inner nodule showed an infiltrative growth pattern. One recent study has reported a microscopic infiltrative tumor border in about 40% of surgically resected PanNETs, which was associated with higher tumor grades, larger tumors, more metastatic lymph nodes, higher American Joint Committee on Cancer stage groups, and the presence of lymphovascular and perineural invasions [ 7 ]. However, the clinicopathologic significance of a microscopic infiltrative tumor border in a PNEMT is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, tumor cells in the inner nodule showed an infiltrative growth pattern. One recent study has reported a microscopic infiltrative tumor border in about 40% of surgically resected PanNETs, which was associated with higher tumor grades, larger tumors, more metastatic lymph nodes, higher American Joint Committee on Cancer stage groups, and the presence of lymphovascular and perineural invasions [ 7 ]. However, the clinicopathologic significance of a microscopic infiltrative tumor border in a PNEMT is currently unknown.…”
Section: Discussionmentioning
confidence: 99%